2012
DOI: 10.1002/j.1532-2149.2011.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcranial direct current stimulation on pain perception and working memory

Abstract: Previous studies have shown that non-invasive stimulation of the dorsolateral prefrontal cortex (DLPFC) could modulate experimentally induced pain and working memory (WM) in healthy subjects. However, the two aspects have never been assessed concomitantly. The present study was set up to investigate the effects of transcranial direct current stimulation (tDCS) of the DLPFC on thermal pain and WM in the same population of healthy volunteers. In a randomized and balanced order of different sessions separated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 52 publications
4
75
1
1
Order By: Relevance
“…They showed different interventions, which differed in the number of sessions and study design, thus making difficult compare them. Other variables, such as intensity of current, stimulated area, stimulation time and methods used to measure the outcomes were similar, corroborating with protocols used by other authors in different populations that investigated the same outcomes (19,20) . It is known that after stroke may occur a change in synaptic homeostasis, which affects individuals' cognition (21) .…”
Section: Discussionsupporting
confidence: 84%
“…They showed different interventions, which differed in the number of sessions and study design, thus making difficult compare them. Other variables, such as intensity of current, stimulated area, stimulation time and methods used to measure the outcomes were similar, corroborating with protocols used by other authors in different populations that investigated the same outcomes (19,20) . It is known that after stroke may occur a change in synaptic homeostasis, which affects individuals' cognition (21) .…”
Section: Discussionsupporting
confidence: 84%
“…We also found that the Egger's test was not significant. Further, the funnel plot revealed that all studies were inside the boundaries of the funnel and symmetrically distributed (Supplementary Figure 3) and no particular study substantially changed the net result according to sensitivity analysis, which ranged from 0.234 to 0.276 after excluding experiments of Boggio et al (2006) and Mylius et al (2012). (Figure 2) …”
Section: Response Timesmentioning
confidence: 99%
“…Two studies reported that a minority of their participants did not complete the study and withdrew because of side effects such as treatment intolerance (Barr et al, 2013) and headache (Mylius et al, 2012). Data of these participants were not analyzed.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations